KEHARMONISAN HIDUP BERMASYARAKAT MELALUI TOLERANSI DALAM PERSPEKTIF AL-QUR’AN - Herwani Herwani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Building a harmonious life in society requires a serious effort starting from each individual or family as the smallest organization in the community that has duties, roles, and as an initial educational process in instilling the values ​​of tolerance from an early age and also the existence of activities in the community that can encouraging mutual respect for differences, maintaining harmony and unity, sharing, belonging, tolerance, and a strong desire to live in peace. As a pluralistic nation, of course, diversity and differences cannot be avoided in society, but with the same determination, a peaceful, just, prosperous and harmonious life will be created as expected by all levels of society. People are said to live in harmony if interactions or relationships between individuals or groups in society go well with each other, have a sense of solidarity, respect differences, feel mutual need, build cooperation, help and others. Islam as a religion of rahmatan lil alamin and the Qur'an which has always been used as a way of life has taught a lot how to build harmony in society, not only fellow Muslims (ukhuwah Islamiyah) but also how to maintain ukhuwah with fellow humans, even though they have different beliefs (ukhuwah insaniyah). . In the Qur'an there are many verses that teach us to maintain the harmony of social life, including QS. al-Baqarah verse 62 is the command to live in peace and side by side, QS. al-Baqarah verse 139, al-Kafirun verse 6, al-an'am verse 108 about respecting every difference, QS. al-Baqarah verse 256 that there should be no coercion in religion, QS. al-Hujurat verse 13 about the diversity of society and others.